Pemberdayaan Pedagang Sayur Keliling Melalui Program “Abang Sayur” dalam Upaya Peningkatan Penjualan di Era Covid-19 - Dyanasari, Dyanasari; Trianawati, Anis; Arvianti, Eri Yusnita (JAST : Jurnal Aplikasi Sains dan Teknologi, 2022)
This community service program aims to provide counseling about increasing sales of vegetable products through the concept of "Abang Sayur," which pays attention to the quality and marketing methods through online to mobile vegetable traders. At this time, problems were found due to government policies amid the Covid-19 pandemic. Restrictions on movement and space trigger limitations for traders to move during the pandemic, resulting in a decrease in the sales turnover of mobile vegetable traders. With the problems that occur, the solutions offered are to provide direction and strategies to increase sales of vegetable products through online marketing and carry out promotional strategies through social media. The results of this extension activity can help increase farmers' income and sales turnover by up to 70%, better packaging, selling labels, financial reports, and product sales through online marketing on Whatsapp Business.ABSTRAKProgram pegabdian masyarakat ini bertujuan untuk memberikan penyuluhan tentang peningkatan penjualan produk sayuran melalui konsep “abang sayur”, yaitu memperhatikan kualitas dan cara pemasaran melalui online kepada pedagang sayuran keliling. Pada saat ini, permasalahan ditemukan akibat kebijakan pemerintah ditengah pandemi Covid-19. Pembatasan gerak dan ruang memicu keterbatasan pedagang untuk bergerak di masa pandemi sehingga terjadinya penurunan omset penjulan pedagang sayur keliling. Dengan adanya permasalahan yang terjadi maka solusi yang ditawarkan yaitu memberikan arahan dan strategi peningkatan penjualan produk sayur melalui pemasaran online dan melakukan stategi promosi melalui sosial media. Hasil dari kegiatan penyuluhan ini dapat membantu meningkatkan pendapatan petani dan omset penjualan hingga 70%, pengemasan menjadi lebih baik, pemberian label jual, memiliki laporan keuangan dan penjualan produk melalui pemasaran online di Whatsapp Business